14C-Based source assessment of soot aerosols in Stockholm and the Swedish EMEP-Aspvreten regional background site - Andersson, August; Sheesley, Rebecca J.; Kruså, Martin; Johansson, Christer; Gustafsson, Örjan (Atmospheric Environment, 2011)
Combustion-derived soot or black carbon (BC) in the atmosphere has a strong influence on both climate and human health. In order to propose effective mitigation strategies for BC emissions it is of importance to investigate geographical distributions and seasonal variations of BC emission sources. Here, a radiocarbon methodology is used to distinguish between fossil fuel and biomass burning sources of soot carbon (SC). SC is isolated for subsequent off-line 14C quantification with the chemothermal oxidation method at 375 °C (CTO-375 method), which reflects a recalcitrant portion of the BC continuum known to minimize inadvertent inclusion of any non-pyrogenic organic matter. Monitored wind directions largely excluded impact from the Stockholm metropolitan region at the EMEP-Aspvreten rural station 70 km to the south-west. Nevertheless, the Stockholm city and the rural stations yielded similar relative source contributions with fraction biomass (fbiomass) for fall and winter periods in the range of one-third to half. Large temporal variations in 14C-based source apportionment was noted for both the 6 week fall and the 4 month winter observations. The fbiomass appeared to be related to the SC concentration suggesting that periods of elevated BC levels may be caused by increased wood fuel combustion. These results for the largest metropolitan area in Scandinavia combine with other recent 14C-based studies of combustion-derived aerosol fractions to suggest that biofuel combustion is contributing a large portion of the BC load to the northern European atmosphere.
id: 2148